80.7k views
1 vote
Would this be correct even though I didn’t use the chain rule to solve?

Would this be correct even though I didn’t use the chain rule to solve?-example-1
User Ryantxr
by
6.2k points

1 Answer

5 votes

Answer:

Dy/Dx=1/√ (2x+3)

Yeah it's correct

Explanation:

Applying differential by chain differentiation method.

The differential of y = √(2x+3) with respect to x

y = √(2x+3)

Let y = √u

Y = u^½

U = 2x +3

The formula for chain differentiation is

Dy/Dx = Dy/Du *Du/Dx

So

Dy/Dx = Dy/Du *Du/Dx

Dy/Du= 1/2u^-½

Du/Dx = 2

Dy/Dx =( 1/2u^-½)2

Dy/Dx= u^-½

Dy/Dx=1/√ u

But u = 2x+3

Dy/Dx=1/√ (2x+3)

User Jiaweizhang
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.